The New Labor Press. Journalism for a Changing Union Movement - Verzuh, Ron (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "The New Labor Press. Journalism for a Changing Union Movement," edited by by Sam Pizzigati and Fred J. Solowey.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z